Improving Provisioning of an Inpatient Portal: Perspectives from Nursing Staff - Gaughan, Alice A.; Walker, Daniel M.; Sova, Lindsey N.; Vink, Shonda; Moffatt-Bruce, Susan D.; McAlearney, Ann Scheck (Applied Clinical Informatics, 2022)
Background Inpatient portals are recognized to provide benefits for both patients and providers, yet the process of provisioning tablets to patients by staff has been difficult for many hospitals.Objective Our study aimed to identify and describe practices important for provisioning an inpatient portal from the perspectives of nursing staff and provide insight to enable hospitals to address challenges related to provisioning workflow for the inpatient portal accessible on a tablet.Methods Qualitative interviews were conducted with 210 nursing staff members across 26 inpatient units in six hospitals within The Ohio State University Wexner Medical Center (OSUWMC) following the introduction of tablets providing access to an inpatient portal, MyChart Bedside (MCB). Interviews asked questions focused on nursing staffs' experiences relative to MCB tablet provisioning. Verbatim interview transcripts were coded using thematic analysis to identify factors associated with tablet provisioning. Unit provisioning performance was established using data stored in the OSUWMC electronic health record about provisioning status. Provisioning rates were divided into tertiles to create three levels of provisioning performance: (1) higher; (2) average; and (3) lower.Results Three themes emerged as critical strategies contributing to MCB tablet provisioning success on higher-performing units: (1) establishing a feasible process for MCB provisioning; (2) having persistent unit-level MCB tablet champions; and (3) having unit managers actively promote MCB tablets. These strategies were described differently by staff from the higher-performing units when compared with characterizations of the provisioning process by staff from lower-performing units.Conclusion As inpatient portals are recognized as a powerful tool that can increase patients' access to information and enhance their care experience, implementing the strategies we identified may help hospitals' efforts to improve provisioning and increase their patients' engagement in their health care.
Keywords: patient portals; electronic health record; inpatient portal